Landscape change shifts competitive dynamics between declining at-risk wolverines and range-expanding coyotes, compelling a new conservation focus. (February 2022) - Chow-Fraser, Gillian; Heim, Nicole; Paczkowski, John; Volpe, John P.; Fisher, Jason T.
Abstract: Conservation actions need to target ecological mechanisms of species declines to be effective, but these mechanisms are often opaque. Shifting balance of competition is one pathway to species declines. Competitive coexistence is maintained only where competitive pressures balance across space. As resources change and new resources are introduced or disappear across landscapes, so should competition outcomes. We tested how novel anthropogenic disturbances affect this competitive landscape in a region with a diverse large carnivore community. We modelled fine-resolution spatiotemporal co-occurrence of wolverine ( Gulo gulo ), an at-risk Nearctic facultative scavenger, and other competing carnivores. We posed hypotheses about the different interspecific interactions – competition, predation, and facilitation – that could affect wolverine distribution across a gradient of anthropogenic disturbance. We used an information-theoretic model-selection framework to weigh evidence for hypotheses about the outcomes of interspecific interactions, inferred from habitat selection in relation to co-occurrence or segregation with other carnivores. Wolverine occurrence in space and time was explained by anthropogenic disturbance features and coyote co-occurrence at sites, revealing that coyote occurrence is a synergistic factor with anthropogenic disturbance. Wolverine were generally segregated from coyotes and avoided linear features; however if wolverine and coyotes did co-occur, they were twice as likely to co-occur at sites with linear features. Thus linear features increased opportunity for coyotes—a generalist species thriving in human disturbed landscapes – to compete with wolverines. We suggest this threat of increased competition is a mechanism potentially contributing to broad-scale wolverine range recessions from increasingly disturbed areas. Landscape change manifests as more than just physical disturbances: it alters the ecological processes that structure communities. These processes contribute to declines of species that cannot adapt to the novel disturbance features. We emphasize competition as an overlooked outcome of landscape change that could inform better conservation decisions to stem species declines.